Primary bone metastasis as first manifestation of an unknown primary tumour - García Carretero, Rafael (BMJ Case Rep, 2015)
Unknown primary tumour refers to a group of cancers for which the anatomical site of origin remains occult after detailed investigations. Thanks to sophisticated imaging, immunohistochemical testing and molecular-profiling tools, there is a more accurate approach to unknown primary cancer. Metastasis to bone is not a rare phenomenon, because any tumour can metastasise to bone, so it is a common clinical scenario. The role of clinical history, physical examination, laboratory tests, radiographic studies and immunohistochemistry is critical for a successful diagnostic strategy. Subsets of unknown primary cancers can be identified primarily on the basis of histopathological findings, the pattern of spread and serum markers. New immunohistochemical markers and tissue-of-origin profiles may establish presumable primary sites to unknown primary cancer on the basis of immunohistochemical and molecular patterns. We present a case of a 57-year-old woman without a cancer history, who had primary bone metastasis as the first manifestation of an occult primary tumour.